Novos registros de Ephemerelloidea (Insecta: Ephemeroptera) para o estado de São Paulo - Dias, Lucimar Gomes; Salles, Frederico Falcão; Polegatto, Cleber Macedo; Silva, Rodolfo Mariano; Froehlich, Claudio Gilberto (Biota Neotropica, 2007)
Neste trabalho são apresentados quatro novos registros de Ephemerelloidea para o Estado de São Paulo, Leptohyphes cornutus Allen, Leptohyphes plaumanni Allen, Tricorythodes bullus Allen e Traverhyphes (Traverhyphes) indicator (Needham & Murphy), esta ultima constitui um novo registro para o Brasil. Além dos novos registros, também são ampliadas as áreas de distribuição das espécies Leptohyphodes inanis Ulmer, Traverhyphes (Mocoihyphes) edmundsi (Allen) e Traverhyphes (Mocoihyphes) yuati Molineri, para outros municípios do Estado de São Paulo.

Four new records of Ephemerelloidea for São Paulo State, Leptohyphes cornutus Allen, Leptohyphes plaumanni Allen, Tricorythodes bullus Allen, and Traverhyphes (Traverhyphes) indicator (Needham & Murphy) are presented. The latter species constitutes a new record for Brazil. In addition of the new records, the distribution of the following species are expanded: Leptohyphodes inanis Ulmer, Traverhyphes (Mocoihyphes) edmundsi (Allen), and Traverhyphes (Mocoihyphes) yuati Molineri.
Keywords: Inseto aquático; Efemerida; Leptohyphidae; Melanemerellidae; Aquatic insects; Mayflies; Leptohyphidae; Melanemerellidae